The Case with Primary Amenorrhea Presented with A 46,X,del(X),(q23) - Yüce, Hüseyin; Etem, Ebru; Gürateş, Bilgin; Elyas, Halit (Fırat University, 2005)
Turner's syndrome is the most common chromosomal abnormality in women, affecting 1:2,500 live female births. A variety of structural abnormalities have been identified for the X chromosome. Xq deletions were identified in 3-4.4% of cases with Turner's syndrome. The case presented at short stature, primary amenorrhea, hypoplasic uterus and hyperthyroidism. Case karyotype was determined as 46,X,del(X)(q23) by cytogenetic analysis of peripheral blood. This karyotype was not determined in cases presented with some Turner's syndrome stigmata in the literature. Xq- cases have variable phenotype. The most likely explanation for the variable phenotypic effect of Xq- is to assume that growth gene(s) in Xp or Xq are inactivated similar to skewed X inactivation seen in some X-autosome translocations. Another reason of phenotypic variation, inactivation center(s) and active genes on inactive chromosome could explain the manifestation or the absence of clinical symptoms in X deletions. The role played by the "critical region" (Xq13-q24) in ovarian development is still unclear. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Turner sendromu, yaşayan kadınlarda 1:2500 sıklıkla görülen en yaygın kromozomal anomalidir. Bu güne kadar X kromozomu ile ilgili olarak pek çok yapısal anomali tanımlanmıştır. Xq delesyonlarına, Turner Sendromlu bireylerin %3-4.4'ünde rastlanmaktadır. Sunulan olgu kısa boy, primer amenore, hipoplazik uterus and hipertiroidi göstermekteydi. Probandın karyotipi, periferik kandan yapılan sitogenetik inceleme sonucu, 46,X,del(X)(q23) olarak saptandı. Literatürde bu karyotipe sahip bazı Turner Sendrom stigmatlarını taşıyan olguya rastlanmamıştır. Xq- olgularda fenotip oldukça değişkendir. Bunun en önemli nedenlerinden biri Xp veya Xq'daki gelişim genlerinin bazı X otozom translokasyonlarında görülen bozuk X inaktivasyonuna benzer şekilde inaktive olmasıdır. X kromozom delesyonlarındaki fenotip değişkenliğinin diğer bir nedeni inaktif X kromozom üzerindeki genlerin veya inaktivasyon bölgesinin etkilenmesidir. Ovarian gelişimde Xq13-24 kritik bölgesinin oynadığı rol hala açık değildir. ©2005, Fırat Üniversitesi, Tıp Fakültesi
46,X,del(X)(q23) Karyotipine Sahip Primer Amenoreli Olgu